Pemanfaatan Molase Sebagai Substrat Acetobacter Xylinum Dalam Pengembangan Indikator Perubahan Kesegaran Buah Pisang - Mujahidah, Anindita; Sukainah, Andi; Indrayani (Agricultural Technology Education Study Program, 2023)
The sugar industry, in addition to producing cane sugar, also produces molasses which is the by-product of the sugar bleaching process. This waste still contains a lot of sugar ± 56%. and organic acids. The purpose of this study was to use molasses as a substrate for A. xylinum to be developed as an indicator of banana freshness. Cellulose produced from molasses substrate can be used as material for placing indicators. Freshness indicator has a working principle by observing changes in fruit freshness that are detected due to changes in pH in atmospheric conditions that are increasingly acidic as a result of metabolic activity. The freshness indicator of bananas from cellulose from 20% molasses substrate has different results of changes in the color of the freshness indicator. The method used in this research to apply the BTB compound to the cellulose sheet produced from molasses to be applied to 3 types of bananas (ambon, kepok and raja). Indicators affixed to plantains reach the indicator color change faster than ambon and kepok. Changes in this indicator are in line with physical and chemical changes in bananas which indicate a decrease in freshness. Both in terms of physical and chemical degradation.